Industrial electronics - Petruzella, Frank D. (New York : Glencoe McGraw-Hill, 1996)
An introduction to industrial motors and controls. The book includes coverage of programmable logic controllers (PLCs) and other computer-controlled machines and processes.
Chapter 1: Industrial Safety Chapter 2: Understanding Industrial Electrical Diagrams Chapter 3: Transformers and Power Distribution Systems Chapter 4: Industrial Control Devices Chapter 5: Power Electronics Chapter 6: Industrial Motors and Generators Chapter 7: Relays Chapter 8: Contacts and Motor Starters + Chapter 9: Motor Control Circuits Chapter 10: Types of Control Chapter 11: Process Control Systems Chapter 12: Programmable Logic Controllers (PLCs) Chapter 13: Computer-Controlled Machines and Processes
Includes index.
Keywords: INDUSTRIAL ELECTRONICS